Mercury distribution and transfer in mangrove forests in urban areas under simulated rising sea levels - Xilin You; Xilin You; Lumin Sun; Xiaozheng Chen; Xiaozheng Chen; Yiting Li; Jue Zheng; Jue Zheng; Dongxing Yuan; Junjie Wu; Junjie Wu; Shiyu Sun (Frontiers in Marine Science, 2024)
This study assesses the impact of simulated sea level rise (SLR) on mercury distribution and migration in an urban mangrove wetland on the northern coast of Maluan Bay, Xiamen City, Fujian Province, China. Two adjacent Kandelia obovata mangrove plots with elevations representing current sea level and a 40-cm SLR were examined. Total mercury (THg), methylmercury (MeHg), and mercury isotopes in sediments from different elevations were analyzed to reveal the geochemical behavior of mercury under a simulated 100-year SLR scenario. THg and MeHg distribution in sediments mirrored patterns of biogenic elements (carbon, nitrogen, and phosphorus), suggesting adsorption onto organic matter as the primary entry mechanism. Low-elevation plots showed significantly higher concentrations of THg, MeHg, total organic carbon (TOC), total nitrogen (TN), and total phosphorus (TP) compared to high-elevation plots. Mercury isotope characteristics indicated that the primary mercury source was anthropogenic emissions from surrounding lands, entering the wetland from both landward and seaward directions. The study highlights the crucial role of mangrove wetlands in mercury pollution control and nutrient cycling under SLR conditions. Results suggest that SLR enhances the retention capacity of mangrove wetlands for THg, MeHg, and nutrients. This research provides a scientific basis for mangrove conservation and restoration, offering new insights into the geochemical behavior of mercury in vegetated intertidal ecosystems in the context of climate change.